HUKUM PEMBULATAN TIMBANGAN BERDASARKAN TINJAUAN KOMPILASI HUKUM EKONOMI SYARIAH (KHES) PADA USAHA PENATU DI DESA PAL IX KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Ria Rifna Sukma; Rahmat Rahmat; Abu Bakar (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2021)
Abstract The purpose of this research in the rounding scale law is how the practice of the rounding scale in the laundry business and how according to the Sharia Economic Law Compilation (KHES) deals with the issue of the laundry business. This research method uses field research and a qualitative approach which are part of a case study in which researchers only take one business location in Sungai Kakap Pal IX Village, Kubu Raya Regency, West Kalimantan. Data collection techniques used in this study were interviews, observation, and documentation. The results of this study indicate that the laundry business has a practice of the rounding scale. The laundry owner was working on this intending to facilitate payment times and refunds. The rounding scale in the laundry business in terms of Sharia Economic Law Compilation (KHES) is not following the principle of justice in muamalah because it is not allowed to play with the measure in the transaction. However, the act of rounding and reducing the scale can cause injustice in the transaction for one of the parties. Thus, every business actor must act honestly and fairly, even the small business itself. Dissemination of the results of this study is important. Thus, KHES can function in the rules and arrangements of muamalah to harmonize life together because KHES provides instructions for muamalah in accordance with Islamic principles. Keywords: Laundry Business, Rounding Scales Law, Sharia Economic Law Compilation